Effects of Zr and Sb addition on grain refinement, high temperature creep and hardness in Mg-3Ca alloys / Widyani Darham - Darham, Widyani (2019)
Elemental addition is one method of improving the micro structure in alloys by grain refinement and consequently improving the mechanical properties such as creep resistance and hardness. Creep resistance of Mg alloys depends on the thermal stability of phases formed when alloying elements are added to Mg alloys. Otherwise, grain coarsening and dissolution at temperatures higher than 400 K may cause deterioration in creep properties. This thesis reports on the effects of Zr and Sb addition to as-cast Mg-Ca alloys prepared by argon arc melting. FESEM and XRD were used to analyze the micro structure of the alloys. The grain refinement effects and mechanism by adding Zr and Sb in Mg-Ca alloys and their influences towards creep resistance and hardness of Zr-added and Sb-added Mg-3Ca alloys at elevated temperatures are further discussed. Micro structures in Mg-1.5Ca and Mg-3Ca alloys showed eutectic mixtures containing fine Mg2Ca and α-Mg phases at both interdendritic and inter-grain regions. Micro structural analysis of as-cast Mg–3Ca–xZr (x = 0.3, 0.6, 0.9 wt.%) alloys showed grain refinement with Zr addition, attributed to the growth restriction effect of Zr in Mg–3Ca alloys. Addition of Sb to Mg-3Ca alloys also resulted in refined microstructure with formation of Mg3Sb2 in the interdendritic region. The grain refinement mechanism can be explained by the growth restriction factor (GRF) of the alloying elements in Mg. Rejection of solute into the melt at the solidification front of the solid/liquid interface caused subsequent release of latent heat, raising the temperature of the liquid between the interdendritic regions and allowed growth of dendritic arms. Creep resistance of the Mg-Ca alloys were investigated using impression creep technique at 423 – 523 K under constant stress of 380 MPa. Graphs of indentation depth against time determine the creep rate of samples. Activation energies calculated suggested mechanisms of creep deformation during impression creep tests. Creep resistance for Mg-3Ca alloys were enhanced with addition of Zr and Sb. Addition of Zr to Mg-3Ca alloys showed improved creep resistance due to solid solution strengthening of α-Mg by Zr. The activation energy value of Zr-added Mg alloys suggested that in Zr-added Mg-3Ca, the dislocation climb is assisted by both boundary and core diffusion. Sb addition to Mg-3Ca alloys displayed lower creep rate compared to Mg-3Ca alloy due to the presence of thermally stable Mg2Ca and Mg3Sb2 in the interdendritic region. Qc value of the samples with higher concentration of Sb suggests that the main mechanism during secondary stage creep is the dislocation climb. The hardness of Mg–3Ca–xZr alloys increased as the amount of Zr increased due to grain refinement and solid solution strengthening of α-Mg by Zr. The addition of Sb increased the hardness of Mg-3Ca alloy by grain boundary strengthening and solid solution strengthening. The findings, analysis and discussions of the research in terms of grain refinement, high temperature creep deformation behaviour and hardness properties are summarized at the end of the thesis.